ngaruh Pemberian Pakan Komplit dalam Pakan Basal Lamtoro dengan Imbuhan Zn Biokompleks terhadap Konsumsi dan Kecernaan Lemak Kasar serta Karbohidrat Ternak Kambing Kacang Jantan - Bheo, Godefridus; Rosnah, Upik Syamsiar; Abdulah, Muhammad S. (Animal Agricultura, 2024)
This study aims to determine the effect of complete feeding in lamtoro basal feed with biocomplex Zn addition on the consumption and digestibility of crude fat and carbohydrates in male kacang goats. There are 4 male kacang goats aged between 1-1.5 years with a weight range of 19.1-21.77 mg (average 20.69 mg). Latin Square Design Method (LSDM) with 4 treatment groups and 4 periods repeatedly. The treatments were: P0: Lamtoro 100% (Control), P1: Lamtoro 70% + Corn Straw Silage 20% + Concentrate 10%, P2: Lamtoro 60% + Corn Straw Silage 30% + 10% Concentrate, P3: Lamtoro 50 %+ Corn Straw Silage 40% + 10% Concentrate. The results of statistical analysis showed that treatment had no significant effect (P>0.05) on carbohydrate consumption, fat digestibility and carbohydrate digestibility. While the treatment had a significant effect (P<0.05) on the consumption of crude fat. In conclusion, complete feeding in lamtoro basal feed with Zn biocomplex added at different levels has the same effect on carbohydrate consumption, crude fat digestibility and carbohydrate digestibility in male local goats. Feeding Lamtoro 60% + Corn Straw Silage 30% + 10% Concentrate provides an optimal effect on the level of crude fat consumption.